Formação docente para um ensino de (e sobre) ciências nos anos iniciais do ensino fundamental: possibilidades para alfabetização científica - Bastos, Giséli Duarte (2019)
A scientifically literate individual understands the scientific concepts, the Nature of Science and the interweaving between Science, Technology and Society and, based on these presuppositions, manages to solve day-to-day and world problems. The Scientific Literacy (SL) gives meaning to the Sciences, fostering learning in the area and corroborating with the need for this to be worked since the first years of school. Therefore, it is necessary to invest in the training of teachers who will be responsible for this teaching stage: the Pedagogues. Thus, this study investigates the means to promote SL in the initial training in Pedagogy while aiming at Didactic Transposition of Sciences for the early years of Elementary School. For this effort, three interventions were carried out in the context of initial training between 2016 and 2017, with the first two being carried out in a private Higher Education Institution (HEI), and with the other being carried out in a public HEI, in a total of 92 hours with the students. The interventions were developed by the researcher while playing the role of the main teacher of the classes. In general, the results reinforced the importance and the right of the future Pedagogues to learn the scientific concepts, as it is necessary to invest in an initial training that assists the overcoming of the common sense knowledge. However, the main finding points to the need for the initial training to provide the means for an epistemological clarification of the Sciences for the students of Pedagogy. Therefore, the training must be based on a methodological diversity that gathers theory and practice, shows real possibilities of actions in the classroom, and provides opportunities for reflection on the training itself, its gaps and its incompleteness. When there is an epistemological understanding, other didactic precepts, such as the pedagogical and psychological aspects of the area, were reconfigured and materialized in creative and unpublished didactic propositions produced by future Pedagogues. Therefore, based on the understanding of the Nature of Science, including the political and ethical aspects that surround it, as well as the typical procedures of the scientific doing, it is concluded that the students were more confident and able to transpose didactically the knowledge of Natural Sciences to the children, while autonomously aiming at the theoretical concepts and founding an actual Science Teaching based on SL.